Ba Jin xuan ji - Bajin (Si chuan ren min chu ban she)
Di 1 juan. Jia – Di 2 juan. Chun – Di 3 juan. Qiu – Di 4 juan. Wu, yu, dian – Di 5 juan. Hai de meng ; Xi yuan ; Chun tian li de qiu tian – Di 6 juan. Di si bing shi ; Han ye – Di 7 juan. Duan pian xiao shuo xuan – Di 8 juan. San wen sui bi xuan – Di 9 juan. Xin sheng ji qi ta – Di 10 juan. Tan zi ji
Literature. - Cover title also in pinyin: Ba Jin xuanji. - Includes bibliographical references